Sprint skating profile of competitive female bandy players: An analysis of positional and playing-level differences - van den Tillaar, Roland; Pojskic, Haris; Andersson, Håkan (Frontiers in Physiology, 2023)
There is no research examining female bandy players, which creates a gap of knowledge of female skating performance and its determinants with male skating performance, not only in bandy but also in exercise science in general. Therefore, the aim of this explorative study was to investigate position and playing-level differences in the sprint skating performance and anthropometrics of 74 elite female bandy players (age: 18.9 ± 4.1 years; height: 1.67±0.06 m; body mass: 63.2±7.4 kg). Participants were categorised according to playing level (26 elite and 48 junior elite players) and position (22 defenders, 35 midfielders, and 17 forwards). They were tested on their anthropometric characteristics and sprint linear skating profile over 80 m with the split times measured at 10, 20, 40, 50, 60, 70, and 80 m to calculate the average velocities between these different 10 m intervals. Results revealed that elite players had more training experience, were heavier, could accelerate faster, and reached a higher maximal velocity than the junior elite players (9.52±0.37 vs. 8.84±0.40 m/s, respectively). In general, defenders were heavier than forwards, and the elite forwards accelerated faster in the first 10 m than the midfielders (p=0.041). In summary, playing level and position, body mass, and training experience modulated skating sprint performance. The findings suggest that female junior-level players should spend more time developing skating sprint and acceleration abilities to meet the specific demands of playing at the elite level. Moreover, the coaches and professionals who work with female bandy players should be aware that the development of acceleration ability is more important for forwards.